A Multiplex and Colorimetric Reverse Transcription Loop-Mediated Isothermal Amplification Assay for Sensitive and Rapid Detection of Novel SARS-CoV-2 - Juscamayta-López, E. (2021)
This work was supported by the CONCYTEC-FONDECYT Program of Proyectos Especiales: Respuesta al COVID-19 2020-01-01 [grant number 034-2020-FONDECYT] and the National Institute of Health of Peru.